Enhancing Community Participation in Public Services through Participatory Innovation - Dadan Saputra; Rizka Aulia Assaf; Asep Zulkifli Achmad (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The Indonesian government has recognized the importance of community participation in the provision of public services. However, community participation in the public sector is often limited due to various factors, such as lack of access to information, limited resources, and low levels of trust in government institutions. To address these challenges, participatory innovation has been identified as a potential solution to enhance community participation in public services. This study aims to explore the role of participatory innovation in enhancing community participation in public services in Indonesia. Specifically, this study seeks to identify the factors that facilitate or hinder the implementation of participatory innovation and to provide insights for public sector organizations to implement participatory innovation effectively. This study adopts a qualitative research approach. Semi-structured interviews were conducted with public sector officials and members of the community who have experience with participatory innovation in the public sector. The data collected from the interviews were analyzed using thematic analysis. Results: The findings of this study suggest that participatory innovation can enhance community participation in public services in Indonesia. The implementation of participatory innovation has resulted in several positive outcomes, such as increased trust in government institutions, improved access to information, and increased community involvement in decision-making processes. However, the implementation of participatory innovation also faces several challenges, such as a lack of resources, limited capacity of public sector officials, and bureaucratic culture.